Levels of clinical condom failure for anal sex: A randomized cross-over trial - Siegler, Aaron J. (EClinicalMedicine, 2019)
BACKGROUND: Men who have sex with men (MSM) face a 28-fold higher risk of HIV acquisition than men who have sex with women (MSW). Condoms are the most accessible prevention method, with billions produced annually. Due to potentially high clinical failure, international regulatory agencies do not approve condoms for anal sex. This trial sought to provide data regarding approval of condoms for anal sex. METHODS: We conducted a blinded, crossover randomized trial among MSM and MSW in Atlanta, Georgia, USA. Crossover conditions were standard condoms, thin condoms, and condoms fitted to each user's penile dimensions. The primary outcome was total clinical failure (slippage and/or breakage), assessed using an intention-to-treat analysis. A mixed methods model assessed differences in odds of failure. The study is registered with ClinicalTrials.gov, NCT02753842, and is completed. FINDINGS: We enrolled 252 MSM and 252 MSW between May 19, 2016 and May 2, 2017. Participants reported a total of 4884 anal or vaginal sex acts using study-provided condoms. For all crossover conditions, clinical failure was lower for anal sex (0•7%, 16/2351) than for vaginal sex (1•9%, 48/2533), (odds ratio 0•40, 95% confidence interval 0•21, 0•75, p < •001)00. There was no difference in odds of failure for anal sex acts between the different types of condoms. Due to study design, nearly all anal sex acts used condom-compatible lubricant (98•3%), yet only a minority of vaginal sex acts (41•6%) used lubricant. Sex acts for which lubricant was used had lower failure for both anal and vaginal sex, with no difference in odds of failure between them. INTERPRETATION: In the largest trial of effectiveness of condoms for anal sex to date, we found remarkably low levels of failure. Condoms should be approved by regulatory agencies for anal sex. Clinicians may recommend condoms as a highly efficacious HIV and STD prevention tool for anal sex. Differences between failure for anal and vaginal sex were likely due to differential use of lubricant. Condom promotion programs should consider providing additional lubricant for all condoms distributed.